Karol Marks a powstanie styczniowe - Ciolkosz, Adam (Londyn: Democratic Press and Liberty Publications, 1963)
"Adam Ciolkosz Bibliotheek Camille HuysmansBrochure handelt over de januari-opstand in 1863 in Polen"